Supplier Selection and Ranking Towards Sustainable Procurement with Multiple Decision Makers - Samaranayake, P.; Nagalingam, S.; Laosirihongthong, T. (IEEE International Conference on Industrial Engineering and Engineering Management, 2019)
The paper proposes a holistic selection and ranking approach for supplier evaluation and purchasing order allocation among suppliers who meet acceptable triple bottom line (TBL) performance. Supplier ranks are developed using judgements from multiple decision-makers. Purchasing order allocation among the ranked suppliers is determined using a linear programming (LP) model, which minimizes the total purchasing cost subject to multiple TBL based constraints. This research enables decision-makers to incorporate sustainability conditions in the supplier evaluation as the basis for best practice with an industry friendly approach, which relies on input from key functional units for a holistic organization wide decision. The proposed approach is expected to motivate decision-makers to consider sustainable perspectives in supplier evaluation and order allocation processes in a global supply chain. This paper illustrates the applicability of the approach using a cement-manufacturing scenario in an emerging economy.